Sharing dan Penyuluhan tentang Bahaya Narkoba di Lembaga Pemasyarakatan Khusus Anak (LPKA) Provinsi Papua - Mona Safitri Fatiah; Yane Tambing; Apriyana Irjayanti; Semuel Piter Irab; Renti Br Tompul; Auriel Matui; Ita Namantar; Mercy Malamba; Maria Mano; Hasna Laday (I-Com: Indonesian Community Journal, 2024)
The abuse of Class I drugs among adolescents in Papua Province and the high number of cases mean that this service is carried out with the aim of sharing and counseling about the dangers of drugs in LPKA Papua Province. Method. This activity was carried out for one day on May 5, 2023, at the Keerom Regency Children's Prison. The target of this activity was 26 juvenile prisoners. The methods of this activity are: question and answer (sharing activities with child prisoners), public health education (Penkesmas) (counseling about the dangers of drugs), and data collection (taking data on the characteristics and knowledge of child prisoners). After the data is collected, it is analyzed using STATA 24 software. Results: Most of the children (50%) detained in prison, 13-year-olds with the most education, graduated from high school (SMA) by 53.8%, and there was an increase in knowledge by 23.4% before and after counseling. Conclusion: There is an increase in children's knowledge, and the most consumed and circulating drug is marijuana.